Sustainable Development and Management of Groundwater in Varanasi, India - Omar P.J.; Dwivedi S.B.; Dikshit P.K.S. (My University, 2025)
Groundwater is the main source of drinking water for half of the world’s population. Therefore, it is very important to conserve and manage this resource. Sustainable development and management of groundwater resource mean to the efficient management of the existing groundwater resources to meet the requirement of the present and future demand without affecting the risk associated with the damage to aquifer physical characteristics. In this paper, Varanasi was taken for the study of groundwater and its sustainable development. Varanasi is the oldest living city, situated on the bank of the holy river Ganga. Varanasi is the third most congested city of the Uttar Pradesh as per census 2011. Due to its religious importance, groundwater extraction is increasing day by day. A steady state of groundwater model was developed for the study area using groundwater flow modelling programme. This model was built in three layers to simulate the different type of soil layers. For conceptualization of the model, different layers and maps were prepared in GIS environment. Data collection was done in the field, and aquifer data was provided by different government organizations. For preparing maps, Landsat 8 satellite imagery was used and for DEM SRTM data was used. Modelling results were also calibrated and validated with the field data. Results reveal that Kashi Vidya Peeth block of the Varanasi is the most groundwater vulnerable regions. Results of this study are very helpful in applying sustainable development and management strategies for the groundwater. © 2020, Springer Nature Singapore Pte Ltd.